КРЕДИТ-МОДУЛЬ ТИЗИМИДА ТАҲСИЛ ОЛАЁТГАН ТЕХНИКАВИЙ ЙЎНАЛИШ ТАЛАБАЛАРИ УЧУН ФАН ДАСТУРИНИ ЯРАТИШ ТЕХНОЛОГИЯСИ - Мухаммедов, Ш.М. (SCIENCE and SOCIETY, 2021)
The article considers that one of the urgent tasks of the existing education system is to bring education in line with world standards. The ways of introducing a credit-modular system into the education system based on European standards are described. Methods used in the training of technology teachers according to the credit-modular system in higher education, including the sequence of developing a materials science program. When creating a scientific program, its features were taken into account. The advantages of the credit-modular system in higher education are also described and recommendations are given.
Keywords: Credit module; education system; educational standards; discipline programs; study volume; self-study; number of credits; distance learning; training platform